Ganoderma tsugae Extract Inhibits Growth of HER2-Overexpressing Cancer Cells via Modulation of HER2/PI3K/Akt Signaling Pathway. (7th April 2013) - Kuo, Han-Peng; Hsu, Shih-Chung; Ou, Chien-Chih; Li, Jhy-Wei; Tseng, Hsiu-Hsueh; Chuang, Tzu-Chao; Liu, Jah-Yao; Chen, Shih-Jung; Su, Muh-Hwan; Cheng, Yung-Chi; Chou, Wei-Yuan; Kao, Ming-Ching
Abstract : Ganoderma, also known as Lingzhi or Reishi, has been used for medicinal purposes in Asian countries for centuries. It is a medicinal fungus with a variety of biological properties including immunomodulatory and antitumor activities. In this study, we investigated the molecular mechanisms by which Ganoderma tsugae (GT), one of the most common species of Ganoderma, inhibits the proliferation of HER2-overexpressing cancer cells. Here, we show that a quality assured extract of GT (GTE) inhibited the growth of HER2-overexpressing cancer cells in vitro and in vivo and enhanced the growth-inhibitory effect of antitumor drugs (e.g., taxol and cisplatin) in these cells. We also demonstrate that GTE induced cell cycle arrest by interfering with the HER2/PI3K/Akt signaling pathway. Furthermore, GTE curtailed the expression of the HER2 protein by modulating the transcriptional activity of the HER2 gene and the stability/degradation of the HER2 protein. In conclusion, this study suggests that GTE may be a useful adjuvant therapeutic agent in the treatment of cancer cells that highly express HER2.